Chaucer and the Social Contest (Routledge Revivals). - Knapp, Peggy (Routledge revivals., 2012)
First published in 1990, Chaucer and the Social Contest takes a fresh view of The Canterbury Tales, by placing the storytelling contest among the Canterbury pilgrims within the larger social contests in the changing England of the late fourteenth century. The author focuses on three crucial fields of contention: the division of social duties into the three estates, the controversies around Wycliffite thought and practice, and the roles of women. Drawing on recent literary theory, particularly Bakhtin and Foucault, Peggy Knapp offers both a reading of nearly all the tales and an argument about.